The Pauson–Khand Mechanism Revisited: Origin of CO in the Final Product1. Issue 7 (21st January 2014) - Lesage, Denis; Milet, Anne; Memboeuf, Antony; Blu, Jérôme; Greene, Andrew E.; Tabet, Jean‐Claude; Gimbert, Yves
Abstract The mechanism of the Pauson–Khand reaction has been studied by mass spectrometry and it has been found, through ion‐molecule reaction with 13CO, that the carbon monoxide incorporated into the product cyclopentenone is one that has been retained within the complex. Theoretical and kinetic calculations support this finding, which provides a complementary explanation for the effect of Pauson–Khand promoters.